Pengaruh Literasi Keuangan, Inklusi Keuangan dan Gaya Hidup Terhadap Pengelolaan Keuangan Wanita Karir di Kabupaten Bekasi - Rudi Junaedi; Nani Hartati (Jurnal Riset Akuntansi Politala, 2023)
This study aims to determine the effect of financial literacy, financial inclusion and lifestyle on the financial management of career women in Bekasi Regency. This study uses independent variables of financial literacy, financial inclusion, and lifestyle and the dependent variable is financial management. The population used in this study is career / working women in Bekasi district, namely 665,070 people. The number of samples was determined by the Slovin formula with an error rate/margin error of 5% or 0.05 so that it obtained 400. The sample collection technique with non-profitability sampling and tested with SPSS software version 23. This study concluded that based on the results of the hypothesis test (t test) that financial management is significantly influenced by financial literacy, financial inclusion, and lifestyle.